Estimating the potential impact of the UK government’s sugar reduction programme on child and adult health: modelling study - Amies-Cull, B; Briggs, A; Scarborough, P (BMJ Publishing Group, 2019)
Objective To estimate the impact of the UK government’s sugar reduction programme on child and adult obesity, adult disease burden, and healthcare costs. Design Modelling study. Setting Simulated scenario based on National Diet and Nutrition Survey waves 5 and 6, England. Participants 1508 survey respondents were used to model weight change among the population of England aged 4-80 years. Main outcome measures Calorie change, weight change, and body mass index change were estimated for children and adults. Impact on non-communicable disease incidence, quality adjusted life years, and healthcare costs were estimated for adults. Changes to disease burden were modelled with the PRIMEtime-CE Model, based on the 2014 population in England aged 18-80. Results If the sugar reduction programme was achieved in its entirety and resulted in the planned sugar reduction, then the calorie reduction was estimated to be 25 kcal/day (1 kcal=4.18 kJ=0.00418 MJ) for 4-10 year olds (95% confidence interval 23 to 26), 25 kcal/day (24 to 28) for 11-18 year olds, and 19 kcal/day (17 to 20) for adults. The reduction in obesity could represent 5.5% of the baseline obese population of 4-10 year olds, 2.2% of obese 11-18 year olds, and 5.5% of obese 19-80 year olds. A modelled 51 729 quality adjusted life years (95% uncertainty interval 45 768 to 57 242) were saved over 10 years, including 154 550 (132 623 to 174 604) cases of diabetes and relating to a net healthcare saving of £285.8m (€332.5m, $373.5m; £249.7m to £319.8m). Conclusions The UK government’s sugar reduction programme could reduce the burden of obesity and obesity related disease, provided that reductions in sugar levels and portion sizes do not prompt unanticipated changes in eating patterns or product formulation.